Dampak Perdagangan Lintas Batas Terhadap Perekonomian Masyarakat Lokal (Studi Kasus: Wilayah Perbatasan RI-PNG di Distrik Muara Tami) - Sinyo Gamma Timisela (Jurnal Ekonomi dan Studi Pembangunan, 2015)
Some things are concerns in this study is to see what factors are the main attraction for people of PNG to spend their money in Indonesia (Skow-Wutung market), so the business man in downtown Jayapura initiative to trade with the people of PNG directly in the region border. Obviously with dependencies on Indonesian products, directly open opportunity for Indonesia to market their national products and local products, so that people on the border of the State was able to improve its economic status. This research using SWOT analysis to found what Strengths, Weaknesses, Opportunities and Treats faced in border area development. The result of this analysis found that border area in District Muara Tami is at 1st Quadrant, that means aggressive growth in the region can be achieved by using the strengths and opportunities that exist, Although there are weaknesses and threats but do not close the opportunity for the development of the trade sector to grow in this region even though they are still informal.Keywords: Cross-Border Trade, SWOT Analysis